Isolation of bacteria with bioremediation potential and analysis of bacterial communities in an area affected by an oil spill in Condorcanqui (Amazonas, Peru) - Castillo Rogel, Rosita T. (2020)
The use of oil and its derivatives has been intensified by the current high energy demand, but brought with it the increase in environmental accidents such as fuel spills that negatively affect ecosystems. In those environments there are microorganisms capable of surviving such conditions and using petroleum hydrocarbons as a source of carbon and energy; those can be used in bioremediation, with an eco-friendly and cost-effective approach. In this work, bacterial strains with bioremediation potential were isolated and identified in culture media supplemented with oil from an area contaminated from an oil spill in the Peruvian Amazon; also was done out the characterization of the bacterial community   by independent analysis of culture by means of next generation sequencing directed to the 16S rRNA gene. The isolated bacterial strains were identified as Acinetobacter rudis, Enterobacter cloacae, Klebsiella oxytoca, Morganella morganii, Proteus hauseri, Proteus terrae, Proteus vulgaris (2), Pseudomonas koreensis, Pseudomonas moraviensis, Pseudomonas prosekii y Serratia marcescens (2). The culture-independent analysis detected the Proteobacteria and Bacteroidetes phylum as predominant in water and soil contaminated with hydrocarbons; Likewise, the taxonomic allocation at the family level highlighted the groups Flavobacteriaceae, Moraxellaceae, Verrucomicrobia and Acetobacteraceae as the most abundant, in addition to the genera Acinetobacter, Flavobacterium and Geobacter present in both samples. In this way, the main groups involved in the degradation of petroleum hydrocarbons were determined using culture-dependent and independent techniques.